Steroid Profiling as an Additional Tool to Confirm One-Sided Hormone Overproduction in Primary Aldosteronism: A Case Report - Chatzitomaris, Apostolos; Eisenhofer, Graeme; Williams, Tracy Ann; Worms, Otari; Nicolas, Volkmar; Reincke, Martin; Klein, Harald H. (Frontiers in Endocrinology, 2019)
Primary aldosteronism (PA) is the leading cause of secondary hypertension. The source of aldosterone hypersecretion is often due to a unilateral aldosterone-producing adenoma, and unilateral laparoscopic adrenalectomy is recommended in such patients. Before surgery, confirmation of unilateral hypersecretion is necessary. This is optimally performed by adrenal venous sampling (AVS). However, AVS is not always successful e.g. due to difficulties in the cannulation of the right adrenal vein. Here we present the case of a 53-year-old female patient with primary aldosteronism, a left-sided adrenal mass and an inconspicuous right adrenal. AVS was performed, but cannulation of the right adrenal vein failed. Therefore, aldosterone hypersecretion also of the right adrenal could not be excluded despite higher aldosterone concentrations in the left renal and adrenal vein. To increase the certainty that the left sided adrenal mass was the source of aldosterone hypersecretion, steroid profiling was performed in a sample from the inferior vena cava. This revealed markedly elevated levels of 18-oxocortisol, 18-hydroxycortisol, 11-deoxycorticosterone and 11-deoxycortisol, a steroid profile that strongly suggested that the left sided adrenal mass was an aldosterone producing adenoma, most likely due to a somatic KCNJ5 mutation. Following unilateral adrenalectomy, CYP11B2 immunohistochemistry and genetics analysis of the resected adrenal confirmed a solitary aldosterone-producing adenoma with intense aldosterone synthase expression, which harbored a previously described KCNJ5 Phe154Cys mutation. Biochemical and clinical cure was confirmed 6 months postoperatively.